(untitled) (Proceedings of the International Conference on Future of Education, 2021)
The benefits of rubrics as teaching learning tools have been identified specifically for performance-based assessment in language. In Indonesia, the ability to produce quality written work has become a necessity to complete higher education but it remained unclear how learning and assessment on this area were conducted. This paper focused on exploring the use of rubrics by four non-native teachers’ working for a private ESL school in Indonesia for assessing students’ writing tasks. The study investigated how the teachers’ current practice and how they approached rubrics for assessing writing by means of both closed and open-ended surveys. Additionally, an analysis of the assessed essay against the rubrics was conducted to identify interrater reliability. The results showed that the teachers had positive attitude towards rubrics, used rubrics regularly and approached rubrics in a similar fashion which was to use them as an assessment tool but not learning tool. There was an identified interrater inconsistency in the scoring results. Additionally, the teachers put a lot more focus on Grammar, Spelling and Punctuation category than on the other two categories (Function & Content, and Cohesion & Coherence). The implication of the study calls for more effective use of rubrics as teaching and learning tools by the teachers as well as the provision of teacher training which enable the teachers to do so and consequently resulting in improvement of interrater reliability